In Vitro Somatic Embryogenesis and Regeneration of Cayenne Pepper (Capsicum frutescens) from West Sumatra - Renfiyeni, Renfiyeni; Yora, Muharama; Meyuliana, Aulia (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
The development of superior cultivars and the availability of high-quality seedlings require stable in vitro propagation. This study evaluated the effectiveness of different culture media for the in vitro propagation of local West Sumatra cayenne peppers using a Completely Randomized Design with eight treatments and six replications. Further testing used the Duncan Multiple Range Test. This research was conducted in the tissue culture laboratory of Mahaputra Muhammad Yamin University, Solok, West Sumatra. Callus initiation and shoot regeneration were conducted on MS medium with various auxin–cytokinin combinations, while root induction was tested on MS and WPM supplemented with auxins. Explants consisted of the first leaf and epicotyl from 21-day-old chili seedlings. The highest callus induction (100%) was observed on MS medium supplemented with 3 mg/l BAP + 0.5 mg/l IAA and MS medium supplemented with 4 mg/l 2,4-D for both types of explants. The highest embryogenic callus formation (98.45%) was obtained on MS + 3 mg/l BAP + 0.5 mg/l IAA. Optimal shoot regeneration (5.29 shoots) was achieved on MS + 2 mg/l BAP + 1 mg/l NAA, whereas the best root induction occurred on WPM + 1 mg/l NAA.